2017
DOI: 10.2147/ptt.s118348
|View full text |Cite
|
Sign up to set email alerts
|

The metabolomics of psoriatic disease

Abstract: Metabolomics is an emerging new “omics” field involving the systematic analysis of the metabolites in a biologic system. These metabolites provide a molecular snapshot of cellular activity and are thus important for understanding the functional changes in metabolic pathways that drive disease. Recently, metabolomics has been used to study the local and systemic metabolic changes in psoriasis and its cardiometabolic comorbidities. Such studies have revealed novel insights into disease pathogenesis and suggest n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 89 publications
(170 reference statements)
3
33
0
Order By: Relevance
“…Interestingly, the five non-immune system genes whose variations are significantly associated with PsA (i.e., ANXA6, HSD3B7, KCNH7, P4HA2, TNIP1) are enriched in RAC1/PAK1/P38/MMP2, synthesis of bile acids/salts and prostaglandin, metabolism of bile acids, arginine and lipids, and biosynthesis of steroid and collagen pathways. These findings are supported through previous research that has linked many of these pathways with PsA and severe psoriasis cases [41][42][43][44].…”
Section: Gwa Studies: Analysis and Deciphering Of Multiple Susceptibisupporting
confidence: 82%
“…Interestingly, the five non-immune system genes whose variations are significantly associated with PsA (i.e., ANXA6, HSD3B7, KCNH7, P4HA2, TNIP1) are enriched in RAC1/PAK1/P38/MMP2, synthesis of bile acids/salts and prostaglandin, metabolism of bile acids, arginine and lipids, and biosynthesis of steroid and collagen pathways. These findings are supported through previous research that has linked many of these pathways with PsA and severe psoriasis cases [41][42][43][44].…”
Section: Gwa Studies: Analysis and Deciphering Of Multiple Susceptibisupporting
confidence: 82%
“…In addition, we also found increased Lys levels in PS-L skin. The increase in Glu concentration is potentially driven by the increased demand for glutamine during keratinocyte hyperproliferation, rapid protein synthesis and www.nature.com/scientificreports www.nature.com/scientificreports/ enhanced immune cells activity that are characteristic to PS 6,16,17 . Chronic inflammation causes the reduction of Phe conversion to Tyr and, consequently, higher Phe levels could be found in tissues with chronic inflammation 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Elevated levels of Glu, Phe, isoleucine (Ile), proline (Pro), ornithine (Orn), sulfoxidized methionine, ADMA, homocysteine (Hcy), various phosphatidylcholines, alpha ketoglutaric acid, lactic acid and urea were found in the blood of psoriasis patients when compared to the samples collected from healthy persons. Higher concentrations of choline, taurine, Glu, Phe, arachidonic acid, citrulline and 12-hydroxyeicosatetraenoic acid (12-HETE) and increased ratios of Glu to serine (Ser), creatinine to glycine (Gly) and taurine to Ala were found in psoriatic lesional skin compared to non-lesional skin or controls [6][7][8][9][10][11] . Several studies that investigated the levels of specific metabolite classes have been conducted 8,9,12,13 , however, to our best knowledge systematic metabolomic analysis of whole skin biopsies have not been performed yet.…”
Section: Hyperproliferation Is the Main Driver Of Metabolomic Changesmentioning
confidence: 99%
“…There has also recently been increased scientific interest in microbial contributions to healthy skin and cutaneous disorders . Furthermore, metabolomics has been used to study the local and systemic metabolic changes in psoriasis and has revealed novel insights into its pathogenesis and suggested new biochemical signatures . It will be interesting to examine whether GL treatment changes the microbiota of the skin and gut or alters the metabolic signatures of psoriasis.…”
Section: Discussionmentioning
confidence: 99%